SCIENTIFIC SIGNIFICANCE OF INNOVATIVE TECHNOLOGIES FOR ORGANIZING INDEPENDENT LEARNING IN PEDAGOGICAL FIELDS - Azizova Umida Xabibullayevna (Modern American Journals, 2025)
This paper examines the scientific significance of innovative technologies for organizing independent learning in pedagogical fields. Drawing on constructivist and self-regulated learning theories, it argues that digital platforms, adaptive systems, and AI-supported tools can measurably enhance learners’ autonomy, metacognition, and transfer of knowledge to classroom practice. The study synthesizes evidence on learning management systems, flipped-classroom models, microlearning, and gamification, highlighting how analytics and formative e-assessment personalize pacing and feedback. Particular attention is paid to teacher education, where simulations, VR/AR cases, and peer-review platforms develop reflective practice and professional competencies. Methodologically, the work outlines mixed-methods designs (learning analytics + validated self-regulation scales + performance tasks) to isolate technology effects from confounds such as prior achievement and digital literacy. The paper also addresses equity, accessibility, and academic integrity, proposing scaffolds for students with diverse needs and clear policies for ethical AI use. Limitations include variability in institutional support and the need for longitudinal designs. The conclusion presents a framework linking tool features to pedagogical functions (modeling, practice, feedback, reflection) and offers implementation guidelines for curriculum developers and teacher-training programs.
Keywords: Independent learning; teacher education; educational technology; learning analytics; adaptive systems; formative assessment; metacognition; flipped classroom; microlearning; gamification; AI in education.